Three approaches to the connection between modernisation and traditionalism: a case study of the acquisition of academic education among ultra-Orthodox and Bedouin women. Issue 3 (2nd July 2016) - Kalagy, Tehila
Abstract: The current study investigates the way conservative societies confront the modernity process in the pursuit of higher education for women. Women in conservative societies serve as unique signifiers during processes of familial and societal change within their communities. The central thesis of this paper is an alternative approach to the evaluation of modernity changes occurring in religious and traditional societies, in light of developments in the Jewish ultra - Orthodox communities throughout Israel and the Bedouin community in the Negev. This new perspective could have a decisive influence on relations between minority conservative groups and the majority group in which they live, in the face of societal shifts.